Employees usage of communication technology during non-work hours: a study on higher educational institutions In Malaysia - Haque, A. K. M. Ahasanul; Anwar, Naila; Tarofder, Arun Kumar; Azam, Ferdous (Science & Engineering Research Support Society, 2020)
In today’s technology-driven world, an understanding regarding the use of communication technology has emerged as a crucial aspect. Therefore, this study took the initiative of comprehending this phenomenon in the context of the education sector, particularly in the Malaysian setting. The population consists of employees working in the different educational institutions in Malaysia. A random sampling method was used for the purpose of collecting the required data. The sample size of the study was 221. Later, the structural model was verified and the hypotheses were tested through SEM. The results of the study have unveiled that several aspects, specifically job engagement, job satisfaction and life satisfaction are favourably associated to each other and in turn, job satisfaction shares a meaningful relationship with the usage of communication technology. Therefore, it can be concluded that the more employees are engaged and satisfied with their job the higher is their satisfaction level with their lives. Finally, this study suggests that the current model can be further developed through the integration of additional relevant constructs.